Highly efficient CFRP anisogrid lattice structures for central tubes of medium-class satellites: Design, manufacturing, and performance. (15th February 2021) - Totaro, G.; Spena, P.; Giusto, G.; De Nicola, F.; Kiryenko, S.; Das, S.
Abstract: A design and manufacturing method for highly efficient CFRP anisogrid lattice shells aiming at central tubes for medium-class satellites is presented in the paper. Central tubes are designed to withstand high inertial forces that are induced by the supported satellite mass and equipment during the launch phase. This requires buckling and material strength other than adequate stiffness. In addition, the typical structure includes several interfaces that are subjected to significant load transfer and need to be properly integrated in the body of the shell. A specifically adapted version of the filament winding technology showed itself to be particularly suitable for this application. The modified process implements a "parallel winding" deposition strategy in conjunction with high modulus dry carbon fibers and resin infusion. However, design and manufacturing issues need to be investigated as a whole in order to minimise the structural weight and be competitive with conventional CFRP structures. In order to demonstrate the performance achievable with an optimal lattice structure, a comprehensive testing campaign was built around two full-scale prototypes: 1) the Technological Model (TM), aimed at the manufacturing process setup and mechanical properties characterization, and 2) the Demonstrator (DM), aimed at global stiffness and strength evaluations culminated with the collapse of the structure.